Social Support and Psychological Well-being of Students who are Compiling their Final Assignments - Umari, Tri; Yakub, Elni; Munawir, Munawir; Hayati, Isnaria Rizki (Kuras Institute, 2024)
The thesis is task end students whose nature must be a condition for graduation. During the work thesis, students experience various obstacles that disturb their psychological well-being. Support social is one of the factors that contribute to Psychological Well-Being. When stressed with academic demands in the form of a thesis, students try to look for support social from the environment family, or friends. Research This uses the approach of descriptive correlational. The population and Sample are Riau University FKIP students. The retrieval technique sample with the Snowball Sampling Technique obtained a sample of 96 samples. The instrument used was the Social Support and Self-Adaptation questionnaire with the results of the instrument validity test with SPSS showing that all the statement items got a value of r-count > r-table, so they were declared valid, and the reliability test with the Cronbach's Alpha test got a value greater than 0.06, so that both The questionnaire was declared reliable.The results of the study found that there is a significant relationship​ between social support social Psychological Well-Being of students who are doing a thesis.